High-Andean wetland of Peru: Floristic diversity, primary net aerial productivity, ecological condition, and carrying capacity (Scientia Agropecuaria, 2020)
Knowledge of the flora and usefulness of Andean wetlands for livestock farming is very scarce, which led to interest in evaluating floral diversity, net aerial primary productivity (NAPP), ecological condition and carrying capacity for alpacas (CCA), in three wetlands of the Shullcas sub-basin in Peru. Floristic readings were taken in 10 quadrants distributed in a radial transect in each wetland and at typical times of the rainy and dry seasons. Phytomass cuts were made in regular periods of 30, 60, 90 and 120 days. Fourteen families of vascular plants with 33 genus and 41 species were found, the Shannon Wiener diversity index fluctuated between 2.28 ± 0.15 and 2.40 ± 0.17, the NAPP presented variation between the months evaluated in a range of 27.39 ± 33.73 to 97.86  ± 47.52 g dry material (DM)/m2, between cut-off periods from 132.12 ± 30.42 to 180.60 ± 32.89 g DM/m2 and between wetlands from 116.71 ± 34.6 to 192.18 ± 22.50 g DM/m2, all in good ecological condition; the CCA fluctuated between 1.38 ± 0.36 and 1.80 ± 0.40 alpacas/ha. The result obtained suggests that wetlands should be assessed for frequent periods in the year as a one-time replacement.
Keywords: wetland; floral diversity; net primary productivity; ecological condition; animal carrying capacity.